Rancang Bangun Sistem Informasi Radiologi Yang Terintegrasi Dengan Picture Archiving Communication System (PACS) - Budiarjo, Teguh; Sutanto, Teguh; Romeo, Romeo (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
Abstract: The existence of RIS is necessary for Imaging System or commonly called Picture Archiving and Communication System (PACS). RIS give feedback information to PACS about patient information and inspection, as well as to be able to track the entire life cycle assessment of the patient, from the initial booking to the end result. PACS and RIS have different tasks and complete each other, whereby RIS handles the functions of text-based computing, including transcription, reporting, ordering, scheduling, tracking, and billing (Huang, 2004).There is RIS workflow processes that can support the performance of the Unit of Radiology. In the Radiology Unit there are several problems, such as: (1) the need for integration between RIS and PACS, which radiographers do not need to input the data on patients who will perform imaging and (2) The need of role screening to ensure that the patient is in the waiting list has come and is ready to conduct the examination. Radiology Information System can be integrated with PACS and DICOM modality that uses a standard 3.0. This is supported by several considerations, such as: (1) an intermediary HL7 can be integrated with the Hospital Information System (HIS), (2) MWL module can be integrated with MPPs Service modality, (3) intermediate HL7 can be integrated with PACS, and (4) Radiology Information system can be implemented and support the performance of the Unit of Radiology.The existence of RIS is necessary for Imaging System or commonly called Picture Archiving and Communication System (PACS). RIS give feedback information to PACS about patient information and inspection, as well as to be able to track the entire life cycle assessment of the patient, from the initial booking to the end result. PACS and RIS have different tasks and complete each other, whereby RIS handles the functions of text-based computing, including transcription, reporting, ordering, scheduling, tracking, and billing (Huang, 2004).There is RIS workflow processes that can support the performance of the Unit of Radiology. In the Radiology Unit there are several problems, such as: (1) the need for integration between RIS and PACS, which radiographers do not need to input the data on patients who will perform imaging and (2) The need of role screening to ensure that the patient is in the waiting list has come and is ready to conduct the examination. Radiology Information System can be integrated with PACS and DICOM modality that uses a standard 3.0. This is supported by several considerations, such as: (1) an intermediary HL7 can be integrated with the Hospital Information System (HIS), (2) MWL module can be integrated with MPPs Service modality, (3) intermediate HL7 can be integrated with PACS, and (4) Radiology Information system can be implemented and support the performance of the Unit of Radiology.